Dual board governance structure and multi-bank performance: a comparative analysis between Islamic banks in Southeast Asia and GCC countries - Nomran, Naji; Haron, Razali (Emerald Group Publishing, 2019)
This paper aims to examine the effect of dual board governance structure, i.e. Shari’ah supervisory board (SSB) and board of directors (BoD), on the performance of Islamic banks (IBs) in Southeast Asia region versus banks in the Gulf Cooperation Council (GCC) region. This study uses a sample of 45 IBs over seven countries covering the period of 2007-2015 based on theGMMestimator – First Difference (2-step). The findings reeal that SSB and BoD for IBs in both regions are segmented in terms of ROA (negative interaction) and integrated in terms of Zakat ratio (Zakat on equity [ZOE]) (positive interaction) only for Southeast Asia region. Furthermore, SSBs positively affect multi-bank performance in Southeast Asia while its effect is absent for GCC. This suggests that Shari’ah governance practices for IBs in Southeast Asia are stronger compared to GCC IBs. Finally, BoD has a significant association with low ZOE for IBs in both the regions. The implications of this research is that the unique agency theory depicted in this study can be inferred when analyzing how dual board structure affects IBs’ performance.Practical implications – For regulators in both regions, SSBs must be given real power to monitor BoD.They should also balance the number of SSB scholars with experience in Shari’ah, as well as in law,accounting and finance. It is also important that such a balance of scholars with PhD in these areas be required for Southeast Asia IBs. For the GCC’s egulators, CG practices need to be improved by giving due importance to SSB characteristics and BoD structure. Though the effects of dual board structure on IBs’ performance has been previously examined in the literature, only SSB size has been used as a single proxy of SSB governance. Furthermore, no empirical evidence is recorded to date on this issue in Southeast Asia and the GCC regions. One of the innovations of this paper is the use of multi-bank performance measures in the IBs performance and corporate governance.